Multiply the brackets giving:
y=x^2-12x+8x-96" "->" "y=x^2-4x-96.......Equation(1)
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 1")
Write as:
y=(x^2-4x)-96+k
where k is a correction that cancels out the error produced by the following process.
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 2")
Take the power from x^2 and move it outside the brackets
y=(x-4x)^2-96+k
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 3")
Discard the x from 4x
y=(x-4)^2-96+k
,~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 3")
halve the -4 inside the brackets
y=(x-2)^2-96+k" "larr" Now we need the "k...Equation(2)
,~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 4")
If you were to expand the bracket you would have:
y=x^2-4xcolor(magenta)(+4)-96+k
The color(magenta)(+4) is the error. If you compare this to Equation(1) you will find that the +4 is not in it
So we set +4+k=0 => k=-4
So Equation(2) becomes:
color(brown)(y=(x-2)^2-96+kcolor(blue)(" "->" "y=(x-2)^2-96-4)
color(green)(y=(x-2)^2-100
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(magenta)("General case")
y= ax^2+bx+c " "->" "y=a(x+b/(2a))^2+c -[a(b/(2a))^2]
" "uarr
" "k